Reduced risk of relapse after long‐term nucleos(t)ide analogue consolidation therapy for chronic hepatitis B. Issue 9 (5th March 2015) - Chi, H.; Hansen, B. E.; Yim, C.; Arends, P.; Abu‐Amara, M.; van der Eijk, A. A.; Feld, J. J.; de Knegt, R. J.; Wong, D. K. H.; Janssen, H. L. A.
Summary Background Before stopping nucleos(t)ide analogue (NA) treatment in chronic hepatitis B (CHB), 6–12 months of consolidation therapy is recommended. Aim To investigate the effect of consolidation therapy on off‐treatment outcomes in CHB patients. Methods We included 94 patients who stopped NA after at least 1 year of therapy. Patients could be HBeAg‐positive or HBeAg‐negative at start‐of‐treatment, but were HBeAg‐negative and had undetectable HBV DNA at time of discontinuation. Consolidation therapy was defined as treatment after the first undetectable HBV DNA (and HBeAg loss for HBeAg‐positive patients) until NA cessation. Results At 3 years, 74% of the start‐of‐treatment HBeAg‐positive and 75% of the start‐of‐treatment HBeAg‐negative patients developed HBV DNA >2000 IU/mL at a single time point, whereas a persistent virological relapse (≥2 tests of HBV DNA >2000 IU/mL 6 months apart within 1 year) developed in 49% of the start‐of‐treatment HBeAg‐positive and 53% of the start‐of‐treatment HBeAg‐negative patients. For both HBeAg‐positive and HBeAg‐negative patients, consolidation therapy of ≥3 years was associated with lower persistent virological relapse rates compared to <1 year (1‐year relapse rate: 25% vs. 54%; P = 0.063 and 24% vs. 57%; P = 0.036, respectively). At 3 years, 9% of the HBeAg‐positive and 14% of the HBeAg‐negative patients became HBsAg‐negative. Prolonged consolidation therapy increased the likelihood of HBsAg loss. Two cirrhotic patients developed hepatic decompensation but both recovered. Conclusions After nucleos(t)ide analogue discontinuation, relapse was common in patients with chronic hepatitis B. Prolongation of consolidation therapy beyond 3 years decreased the risk of persistent virological relapse and increased the likelihood of HBsAg loss.